Use of performance based contracting for road maintenance works in Ghana - Yakubu, Sulemana Hudu (2015)
A dissertation submitted to the Department Building Technology of the Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Masters of Science in Procurement Management,